Ecoprint Training for MGMP High School Biology Teachers to Enrich P5 Activity Planning Skills in Merdeka Curriculum - Susintowati; Muhimmatin, Ifa; Kartika Santi, Triana; Ni’matul Jannah, Iis; Hari Prasetiyo, Totok (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2024)
The Merdeka Curriculum starts in the 2021/2022 school year, and in November 2022, 98% of schools in Banyuwangi Regency have implemented the Merdeka Curriculum. One of the components of the independent curriculum is a program called Program Profil Penguatan Pelajar Pancasila (P5). The P5 project requires teacher skills in filling out materials that refer to P5 competencies, so teachers need to upgrade themselves with various skills. This ecoprint training aims to enable high school biology teachers who are members of MGMP to develop and incorporate ecoprints into their learning process, especially for the P5 Project. Ecoprint training held in the multimedia laboratory and room B5, University of 17 August 1945 Banyuwangi. The training participants were 34 biology teachers who were members of MGMP Biology in Banyuwangi. The training participants enthusiastically participated in a series of activities, and actively practiced. The evaluation results of this training activity show that participants have gained additional experience and knowledge regarding the ecoprint technique. The training participants are committed to practicing it independently and transmitting this experience to students at the participants' home schools through the biology learning process and P5 independent curriculum activities.